Pembangunan Media Penjualan Melalui E-Commerce Platform Tokopedia Pada Usaha Mikro, Kecil, Menengah Keripik Ketela Ngobo - Omar Al Faroq; Dini Rahmayanti (Nanggroe: Jurnal Pengabdian Cendikia, 2022)
The development of information technology with an increase in terms of marketing, in which there are many continuous aspects between human relations in the distribution of its products. a) The method of approach is by visiting the production site and directly meeting the owner of the chip business and we provide some related questions about the productivity and marketing of the products being hawked. b) Creation of a Marketplace page through Tokopedia as an Online sales mediation that will be used as a place to sell ketela chips products c) Formation and management of store pages on Tokopedia by including several link images and adding descriptions of each product that will be hawked and displayed on Tokopedia. d) Distribution of Tokopedia results that have been formed to business owners of ketela chips and provide introduction and education related to the use of Tokopedia and marketing through Tokopedia that has been formed. Tokopedia is here to sell a variety of superior and quality products. Not only in the lower circles, Tokopedia can also provide services for large entrepreneurs. Tokopedia.com is one of the largest digital-based buying and selling companies in Indonesia.In this service in the form of building sales media through the Tokopedia e-commerce platform on micro, small, medium enterprises, Ngobo kettle chips have been carried out properly. From the form of implementation is a teaching and training for the next cadre to develop this boiler cryptic business. Because if it is not continued, it will be able to reduce the benefits with the presence of this business which provides job opportunities to the surrounding community who participate in producing these boiler chips.